2021
DOI: 10.1371/journal.pone.0261233
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of cervical lymph node metastases in patients with papillary thyroid carcinoma: Incremental diagnostic value of dual-energy CT combined with ultrasound

Abstract: Purpose To determine whether dual-energy CT (DECT) has incremental diagnostic value when combined with ultrasound (US) in the diagnosis of metastatic cervical lymph nodes (LNs) in patients with papillary thyroid carcinoma (PTC). Methods This was a single-center retrospective cohort study of patients diagnosed with PTC between October 2019 and August 2020. US features of LNs to include hyperechogenicity, round shape, microcalcification, cystic component, and homogeneous/peripheral vascularity were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The study revealed that combined DECT parameters (AUC = 0.942) significantly surpassed US morphological parameters (AUC = 0.771, p < 0.001) in diagnostic accuracy, with a sensitivity, specificity, and accuracy of 92.9%, 86.2%, and 90.9%, respectively. Similarly, the retrospective assessment by Yoon et al [38] of 102 patients (49 with LN metastases and 53 without) indicated that integrating DECT parameters with US features elevated the diagnostic AUC from 0.890 to 0.941.…”
Section: Comparative Efficacy Of Dect and Other Radiological Modalitiesmentioning
confidence: 90%
See 1 more Smart Citation
“…The study revealed that combined DECT parameters (AUC = 0.942) significantly surpassed US morphological parameters (AUC = 0.771, p < 0.001) in diagnostic accuracy, with a sensitivity, specificity, and accuracy of 92.9%, 86.2%, and 90.9%, respectively. Similarly, the retrospective assessment by Yoon et al [38] of 102 patients (49 with LN metastases and 53 without) indicated that integrating DECT parameters with US features elevated the diagnostic AUC from 0.890 to 0.941.…”
Section: Comparative Efficacy Of Dect and Other Radiological Modalitiesmentioning
confidence: 90%
“…In the realm of thyroid disease, US remains the preferred preoperative imaging modality. However, its operator dependency and limited capacity to visualize deep-seated LNs may compromise the accurate diagnosis of cervical nodal metastasis in PTC patients [2,38]. Li et al [2] compared the diagnostic performance of DECT and US in detecting lateral cervical nodal metastasis in PTC.…”
Section: Comparative Efficacy Of Dect and Other Radiological Modalitiesmentioning
confidence: 99%
“…Therefore, quantification of IC is difficult in areas with mixed tissue types. However, in DLCT, IC can be measured based on iodine uptake per unit volume by iodine-based material decomposition imaging, which is a more realistic representation of IC values (20,21).Tang et al (22) demonstrated through simulation experiments that quantitative IC values derived from DECT are highly consistent with actual iodine deposition in the tissue, suggesting that they represent the true distribution of iodine in the tumor tissue. Following efforts to minimize individual circulation-induced variability, NIC has been shown to be an important marker in a wide range of clinical cancer studies (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%